US Community Colleges: Innovators and Influencers - Hopper, Richard (International Higher Education, 2023)
US community colleges are scrappy, agile, and adaptive. Some recent innovations have been workforce development and microcredentials; a diversification of cost-sharing arrangements for professional development; transition of traditional remedial education toward developmental education; a simplification of administrative hurdles to speed up graduation via guided pathways; and college credit to high school students who take college-level courses through dual and concurrent enrollment. These innovations have influenced the university sector to embrace similar changes.